AS . biuletyn pism związkowych i zakładowych, no. 40, 1981 - Agencja Prasowa "Solidarność", [ed. M. Arasimowicz et al.] (Agencja Prasowa AS z siedzibą w "Mazowszu", 1981)
Creation and circulation: Publication contains reprints of trade union documents and articles from the trade union press.